Rehabilitation of Left Homonymous Hemianopia with Adjacent Palomar Prism Technique and Visual Therapy on Line - Mascaró, Fernando-J. Palomar- (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
We present a case of a female who suffered a right cerebral infarction, which caused a left Homonymous hemianopia. He couldn´t walk alone or do tasks of near vision, as reading. For his rehabilitation, we used Palomar´s prisms and visual therapy on line with stimulation exercises and spatial localization. The patient was able to totally recover the central visual field in one year of treatment, being able to walk alone with the visual far aid.